Handbook of enzyme inhibitors - Zollner, Helmward (Wiley-VCH, 1999)
The proven organization of the work in two parts has been maintained: you can search from enzyme to inhibitor (Part A) and from inhibitor to enzyme (Part B). Useful entries, e.g. on the type of inhibition or the effective concentration are given as well as comments on organisms and products and an extensive documentation of references.